Issue Information. (28th October 2021) - Unknown
Abstract : Cover Photograph: Upper left: Rod‐cell specific induction of green fluorescent protein geneby modified reverse tetracycline‐controlled transactivator, rtTAm, in medaka fish. Upper right: In vivo recording of neuronal activity by a genetically encoded voltage indicator in the zebrafish brain. Middle right: The GONAD method involves in vivo genome editing of early preimplantation embryos in oviducts of pregnant mice or rats. Lower left: Convergent extension cell movements in three notochord explants labelled with two different fluorescent proteins. Control (left panels) and cxcl10‐overexpressing explants (right panels). Lower right: A fluorescent raw image (left side) and a machine learning‐based segmentation image (right side) of Xenopus ectodermal cells.